2024
DOI: 10.1136/bmjopen-2023-082345
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of people with chronic kidney disease regarding digital health interventions that promote healthy lifestyle: qualitative systematic review with meta-ethnography

Thái Bình Trần,
Meghan Ambrens,
Jennifer Nguyễn
et al.

Abstract: ObjectivesDiet and physical activity are crucial for people with chronic kidney disease (CKD) to maintain good health. Digital health interventions can increase access to lifestyle services. However, consumers’ perspectives are unclear, which may reduce the capacity to develop interventions that align with specific needs and preferences. Therefore, this review aims to synthesise the preferences of people with CKD regarding digital health interventions that promote healthy lifestyle.DesignQualitative systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 155 publications
0
0
0
Order By: Relevance
“…While the findings of this review demonstrate the current evidence-base is limited, fourteen registered trials were identified, including 12 RCTs (combined target sample size ~ 3,000 participants) [ 45 – 51 , 61 , 62 , 75 – 77 ].This suggests that the evidence base will soon increase substantially, providing further insight into efficacy, though only where consumer preferences are met [ 78 ]. People living with CKD are interested in digital interventions to manage their condition [ 79 , 80 ], but frequently report a lack of specific advice [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the findings of this review demonstrate the current evidence-base is limited, fourteen registered trials were identified, including 12 RCTs (combined target sample size ~ 3,000 participants) [ 45 – 51 , 61 , 62 , 75 – 77 ].This suggests that the evidence base will soon increase substantially, providing further insight into efficacy, though only where consumer preferences are met [ 78 ]. People living with CKD are interested in digital interventions to manage their condition [ 79 , 80 ], but frequently report a lack of specific advice [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Well-rounded digital interventions are likely to address this important gap. A recent systematic review identified key features to support consumer needs in digital exercise interventions including supporting virtual communities of care, specific education, reminders/monitoring and crucially, the ability to individualise exercise programs [ 78 ]. There were also several studies whose primary outcomes were outside the scope of this review e.g., primary focus on diet or medication with digital support, or activity trackers only without physical activity promotion components.…”
Section: Discussionmentioning
confidence: 99%